Genomic Signatures of Domestication in a Fungus Obligately Farmed by Leafcutter Ants - Leal-Dutra, Caio A.; Vizueta, Joel; Baril, Tobias; Kooij, Pepijn W. [UNESP]; Rødsgaard-Jørgensen, Asta; Conlon, Benjamin H.; Croll, Daniel; Shik, Jonathan Z. (Oxford University Press (OUP), 2024)
The naturally selected fungal crop (Leucoagaricus gongylophorus) farmed by leafcutter ants shows striking parallels with artificially selected plant crops domesticated by humans (e.g. polyploidy, engorged nutritional rewards, and dependence on cultivation). To date, poorly resolved L. gongylophorus genome assemblies based on short-read sequencing have constrained hypotheses about how millions of years under cultivation by ants shaped the fungal crop genome and potentially drove domestication. We use PacBio HiFi sequencing of L. gongylophorus from the leafcutter ant Atta colombica to identify 18 putatively novel biosynthetic gene clusters that likely cemented life as a cultivar (e.g. plant fragment degradation, ant–farmer communication, and antimicrobial defense). Comparative analyses with cultivated and free-living fungi showed genomic signatures of stepwise domestication transitions: (i) free-living to ant-cultivated: loss of genes conferring stress response and detoxification; (ii) hyphal food to engorged nutritional rewards: expansions of genes governing cellular homeostasis, carbohydrate metabolism, and siderophore biosynthesis; and (iii) detrital provisioning to freshly cut plant fragments: gene expansions promoting cell wall biosynthesis, fatty acid metabolism, and DNA repair. Comparisons across L. gongylophorus fungi farmed by 3 leafcutter ant species highlight genomic signatures of exclusively vertical clonal propagation and widespread transposable element activity. These results show how natural selection can shape domesticated cultivar genomes toward long-term ecological resilience of farming systems that have thrived across millennia.